Nippon Cinema at the digital turning point - Marek Bochniarz (Przestrzenie Teorii)
This article is a review of a book written by Mitsuyo Wada Marciano – Japanese Cinema in the Digital Age. The author of this book examines the recent developments in the Japanese film industry at the turning point in the development of digital technologies. The book seeks to overcome the western approach to the subject, reinterprets classic films and explores new trends in transnational Japanese cinema (the term was proposed by the author to explain the situation of Japanese films in the context of Asian countries).